Radares Fixos e móveis : uma análise de dados em painel sobre os acidentes de trânsito no município de Porto Alegre - Foletto, Cesar (2014)
The present study has origins in the possibility to evaluate the efficacy of the fixed and mobile speed cameras as a mean to reduce the number of victims in the transit ¬of the biggest streets in the capital city of the state of Rio Grande do Sul, Porto Alegre. To perform such analysis we used data from the Departamento Estadual, de Trânsito (DETRAN/RS), Departamento Autônomo de Estradas e Rodagem (DAER) and from authorities that work in the control of the traffic in the city of Porto Alegre, the Empresa Pública de Transporte e Circulação (EPTC) and the Departamento Estadual de Polícia Judiciária de Trânsito (DPTRAN), these data is available at the portal #DATAPOA. The period extracted from the portal was from January 2008 to December 2012, which makes possible to identify the relation between fixed and mobile enforcement in avenues and the consequences of accidents on these streets, mainly on the severity of the crashes and on the number of injured people. This study has organized the data in a longitudinal panel, allowing the analysis using the Poisson regression technique, which searches for differences between control and treatment groups over time. The results found were very relevant for the analysis of the injuries, and make possible an outlook on the severity of the crashes by the methodology of the severity standardized unit (UPS). The fixed position speed cameras were able to reduce the number of injured and the severity only at the specific location, but did not affect the overall street outcomes. The mobile speed Camera program was able to reduce the number of injuries but only at non rush hours, when the accidents and its outcomes might be influenced more by human factors other than the speed of vehicles. At last, this study could use many variables related to urban transit and verify how each one affect the consequences of an accident, such as, the type of vehicle, the period of the day, climatic conditions and the type of the accident.